Working time and teaching time: composition of the working hours of São Paulo teachers - Barbosa, Andreza; Fernandes, Maria José Da Silva [UNESP]; Cunha, Renata Cristina Oliveira Barrichelo; de Aguiar, Thiago Borges (FapUNIFESP (SciELO), 2021)
Given the difficulty of quantifying how much time teachers actually work, since the official data available often only consider the time spent in the classroom, or the contractual working hours, this paper presents results of a research that analyzed the constitution of the working hours of teachers in the public school system in the state of Sao Paulo. We investigated and problematized the constitution of the working hours of teachers in the final years of elementary and secondary education in the mentioned school network, considering classroom time and extra-class work time. The research in question was carried out in a city in the countryside of São Paulo in two stages: in the first, questionnaires were applied to teachers from thirty schools. In the second, an in-depth qualitative analysis of the data collected in the first stage was conducted through semi-structured interviews with a group of thirteen teachers. The results obtained show that the working time of teachers is much longer than the official time that their working day consists of, which means that a great deal of the time devoted to extra-class work is unpaid, although it serves to perform essential activities for teachers to work with students. It was also highlighted that the teachers who participated in the survey have expanded their working hours to compensate for the low salaries received, which is also added to the increased work demand and the devaluation of teachers, as reported by them.
Tempo de trabalho e de ensino: composição da jornada de trabalho dos professores paulistas
Keywords: Condições de trabalho docente; Extracurricular work; Jornada de trabalho docente; Rede pública de ensino paulista; São Paulo public education system; Teaching work conditions; Teaching work hours; Tempo de trabalho; Trabalho extraclasse; Working time